Rancang Bangun Mesin CNC PCB Berbasis Arduino Untuk Mendukung TEFA Jurusan Teknik Informatika - Hermawanto, Fendi; Habibi, Hilda Jaya (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
The State Polytechnic of Banyuwangi in the Strategic Plan 2020-2024 has a target to improve the quality of the curriculum and learning. To achieve these goals, a strategy is to establish a Teaching Factory (TeFa). One of the rapidly growing industries today is the Printed Circuit Board (PCB) manufacturing industry. This is evidenced by the presence of PCB printing websites such as Indomaker and marketplaces like Tokopedia and Bukalapak, which provide PCB printing services according to customer preferences with fast turnaround times. The research supported the development of the Teaching Factory in the Department of Informatics Engineering, Computer Engineering Technology study program. This will be achieved by increasing the number of CNC PCB machines to create a working system that closely resembles real industry conditions. The method used is the Research and Development (R&D) method, which is used to develop a product and test its effectiveness. During the testing of the X, Y, and Z axis movements, the CNC PCB machine was found to move according to the instructions provided by the Candle Software. In the testing of the PCB trace printing configuration using a V 30° router drill bit, the best results were obtained using a Cut Z of 0.15 mm and a Feed Rate of 20 mm/minute. The presence of the CNC PCB machine will facilitate the TEFA of the Department of Informatics Engineering in creating prototypes of a product before it enters the production stage..